Adverse events during supervised exercise interventions in pediatric oncology: a nationwide survey - Gauß, Gabriele; Beller, Ronja; Boos, Joachim; Däggelmann, Julia; Stalf, Hannah; Wiskemann, Joachim; Götte, Miriam (Frontiers in Pediatrics, 2021)
Objectives: Exercise interventions during and after treatment for pediatric cancer are associated with beneficial physical, psychological, and social effects. However, valid data about adverse events (AEs) of such interventions have rarely been evaluated. This retrospective study evaluates AEs that occurred during supervised oncological exercise programs for pediatric cancer patients and survivors.Methods: This Germany-wide study used a self-administered online survey focusing on general program characteristics and AEs retrospectively for 2019. The questionnaire included (a) basic data on the offered exercise program, (b) AEs with consequences (Grade 2-5) that occurred in 2019 during an exercise intervention, (c) number of Grade 1 AEs, (d) safety procedures as part of the exercise programs, and (e) possibility to give feedback and describe experience with AEs in free text.Results: Out of 26 eligible exercise programs, response rate of program leaders was 92.3% (n = 24). Representatives working for Universities (n = 6), rehabilitation clinics (n = 3), acute cancer clinics (n = 12), and activity camps (n = 3) participated. In total, 35,110 exercise interventions with varying duration were recorded for 2019. Six AEs with consequences (Grade 2-3) occurred during exercise interventions after cancer treatment resulting in an incidence of 17 per 100,000 exercise interventions (0.017%). No life-threatening consequences or death were reported and no serious AE occurred during acute cancer treatment. Grade 1 AE occurred with a frequency of 983, corresponding to an incidence of 2,800 per 100,000 interventions (2.8%). Most frequent Grade 1 AE were muscle soreness, circulatory problems, and abdominal pain. The most frequent preventive safety procedures at the institutions were regular breaks, consultations with the medical treatment team, and material selection with low injury potential.Conclusions: Supervised exercise interventions for pediatric cancer patients and survivors seem to be safe and AEs with consequences comparatively rare when compared to general childhood population data. Occurrence of grade 1 AEs was common, however, causality was probably not evident between AEs and the exercise intervention. Future research should standardize assessment of AEs in clinical practice and research, and prospectively register and evaluate AEs that occur in the context of exercise interventions in pediatric cancer patients and survivors.
Gesehen am 08.11.2021